Effect of Fixed Filamentous Media on Wastewater Treatment - Mamun, Abdullah Al; Abdul Rahman, Muhammad Amiruddin; Sayem, S. M. Abu (Global Science Publications, 2021)
Adequate treatment of wastewater is important for the protection of the environment. In many countries, the existing conventional biological wastewater treatment systems are unable to meet the required standards. Therefore, present research focused on the improvement of aerobic wastewater treatment plant by adding readily available cheap media. Plastic filamentous media was used due to the non-biodegradable property. The media length was 5 meter but it was rolled into spiral shape. The average removal of TDS and COD, without the media, was about 35% and 70%. After the media has been added, the removal efficiency improved to 55% and 95%, respectively. The experimental results demonstrated that the use of filamentous media is capable of improving the quality of effluents in wastewater treatment towards a better quality of effluent to be discharged to nature.